QUANTUM MYSTICISM AND SUFI CONSCIOUSNESS: AN INTERDISCIPLINARY PHILOSOPHICAL INQUIRY INTO HAQIQAH AND MA’RIFAH - Iin Inayatul Ummah; Suadi Sa’ad; Kheryadi; Ade Fakih Kurniawan; Jamadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the philosophical relationship between the concepts of haqiqah and gnosis in Sufism with the basic principles of Quantum theory through an interdisciplinary approach. This study is motivated by the growing discussion on the relationship between spirituality and modern science, particularly Quantum theory, which offers a new view of reality, consciousness, and the interconnectedness of the universe. The study uses a qualitative method with a library research approach, analyzing relevant literature sources, such as books, scientific journals, and works on Sufism and Quantum theory. Data are analyzed using content analysis techniques and a comparative approach to find conceptual relationships between the two disciplines. The results show that haqiqah in Sufism can be understood as a potential dimension of spiritual awareness, whereas gnosis is the actualization of spiritual experience as direct, intuitive, and transformative. This concept has philosophical resonance with several Quantum principles, such as superposition, uncertainty, entanglement, the observer effect, and the collapse of the wavefunction. The principle of superposition describes various possible states before actualization, which is analogous to the human inner state before achieving gnosis. The principle of uncertainty demonstrates the dynamics and unpredictability of reality, as does the personal and evolving spiritual journey. Meanwhile, the concept of entanglement demonstrates a universal connectedness that shares conceptual similarities with the principle of monotheism in Sufism. This study concludes that the relationship between Sufism and Quantum Theory is heuristic and philosophical, not an empirical one that demonstrates direct ontological equivalence. Therefore, the analogy between the two should be understood as a conceptual bridge to establish a dialogue between spirituality and modern science without reducing either domain. This research contributes to the development of interdisciplinary studies on consciousness, metatheory, philosophy of science, and Islamic spirituality in the contemporary intellectual context.